2019
DOI: 10.1088/1742-6596/1349/1/012092
|View full text |Cite
|
Sign up to set email alerts
|

Rice husk ash and sewage sludge ash as sustainable replacement material for concrete

Abstract: The development of supplementary cementitious materials (SCMs) has become essential in the advancement of low-cost construction materials for production of self-sufficient housing especially in developing countries. The use of these SCMs as admixtures not only improves concrete properties but protects and conserves the environment by saving energy and natural resources. Thus, studies have been conducted to find the suitability of combination of sewage sludge ash and rice husk ash to replace cement partially in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In the same line of research, Tutur et al. 33 used rice husk ash and sewage sludge ash as a sustainable replacement material for conventional concrete. This work found that there was an increase in the compressive strength of concrete with 10% by mass of the proposed mixture.…”
Section: Theoretical Foundationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same line of research, Tutur et al. 33 used rice husk ash and sewage sludge ash as a sustainable replacement material for conventional concrete. This work found that there was an increase in the compressive strength of concrete with 10% by mass of the proposed mixture.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…Likewise, Sua-Iam et al 32 evaluated the compressive strength of self-compacting concrete by incorporating rice husk ash and foundry sand waste as a fine aggregate replacement in the properties of self-consolidating concrete as a substitute for cement. In the same line of research, Tutur et al 33 used rice husk ash and sewage sludge ash as a sustainable replacement material for conventional concrete. This work found that there was an increase in the compressive strength of concrete with 10% by mass of the proposed mixture.…”
Section: Reinforcing Materials For Aluminum-based Alloymentioning
confidence: 99%
“…Those data were tabulated in table 2. Finding by Nuraini [11] indicated that the strength increased as the curing period increased. This is accurate since the reaction between the organic waste and the cement is still taking place slowly.…”
Section: Compressive Strengthmentioning
confidence: 99%